Diagnosis of the release phase in the discus throw relative to elite throwers’ height - Kailani, Ghazi El; Azab, Mahmoud; Abdel Fattah, Osama; Zureigat, Ayed A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to quantify the correlation between the thrower’s height and the release height ratio. Furthermore, an estimated equation was provided for predicting the optimal release height of the discus based on the thrower’s height. To achieve these goals, a descriptive approach was applied to a sample of 30 top discus throwers who achieved a horizontal displacement of more than 61 m. The results showed a statistically significant relationship (p < 0.05) between the thrower’s height and the release height ratio. In addition, an estimated equation was developed for predicting the optimal release height of the discus relative to the thrower’s height: release height (m) = -46.121 × thrower height (m) + 175.66. These findings suggest that thrower height plays a meaningful role in determining the optimal release height, providing practical guidance for coaches and athletes to improve discus throw performance.